2011
DOI: 10.1111/j.1600-0560.2011.01808.x
|View full text |Cite
|
Sign up to set email alerts
|

Amelanotic melanoma: a detailed morphologic analysis with clinicopathologic correlation of 75 cases

Abstract: Amelanotic melanoma can have a varied appearance both clinically and microscopically. Here, we present our experiences with 75 cases of amelanotic melanoma defined clinically as a non-pigmented lesion and histopathologically as a tumor lacking significant melanization. We evaluated microscopic features such as morphology, mitotic count, nuclear atypia and presence of solar elastosis. Our amelanotic melanomas exhibited the following morphology: epitheloid (72%), spindled (18.7%) or desmoplastic (5.3%). In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
1
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 13 publications
4
67
1
8
Order By: Relevance
“…Other studies have variably reported predilection of amelanotic melanoma for females, 6,7 males 14,30 or neither sex. 31 In unadjusted analyses, we observed that younger (< 50 years) females were more likely than males of a similar age to have amelanotic than pigmented melanoma but there was little difference at older (>50 years) ages.…”
Section: Discussionmentioning
confidence: 91%
“…Other studies have variably reported predilection of amelanotic melanoma for females, 6,7 males 14,30 or neither sex. 31 In unadjusted analyses, we observed that younger (< 50 years) females were more likely than males of a similar age to have amelanotic than pigmented melanoma but there was little difference at older (>50 years) ages.…”
Section: Discussionmentioning
confidence: 91%
“…The amelanotic lesions are usually of the nodular type and are highly undifferentiated. [67] For the above-mentioned reasons, most cases of amelanotic melanomas present at a later stage, though early lesions have also been described. [8] In men, these are commonly found in the trunk while in women these are found commonly in lower limbs.…”
Section: Discussionmentioning
confidence: 99%
“…Al igual que el MM convencional, su ubicación varía según género, siendo más común en el tronco en hombres y extremidades en mujeres. 8 Se clasifican en tres grupos según la cantidad de pigmento observado clínicamente en su superficie: amelanótico, parcialmente pigmentado (<25%) y ligeramente pigmentado (>25%). Se cree que la falta de pigmento traduce una pobre diferenciación.…”
Section: Epidemiologíaunclassified